MONITORING APPLICATION SYSTEM DEVELOPMENT AND EVALUATION OF “PUPR” DEPARTMENT OF GENDER LEADING ACTIVITIES IMPLEMENTATION - Ramacos Fardela; Arif Rizki Marsa; Lilik Suhery; MS Firman Maulana (Universitas Nusa Cendana, 2023)
Monitoring and evaluation are the jobs that are often done by the Payakumbuh Public Works Department to maximize work in the field. The Payakumbuh Public Works and Public Housing (PUPR) Office itself is experiencing difficulties in monitoring and evaluating work in the field that is currently underway and the activities carried out have been realized. So far, office work has been monitored manually one by one because the Payakumbuh (PUPR) does not have an information system that can monitor and evaluate all work simultaneously and provide an overall target picture yet. In activities, especially work at the Payakumbuh PUPR Service, it applies the application of gender mainstreaming (